Hepatitis B Prevalence and Incidence in Greenland: A Population-Based Cohort Study - Børresen, Malene Landbo; Andersson, Mikael; Wohlfahrt, Jan; Melbye, Mads; Biggar, Robert J.; Ladefoged, Karin; Panum, Inge; Koch, Anders (American Journal of Epidemiology, 2015)
Greenland remains a highly endemic area for hepatitis B virus (HBV) infection. This is in sharp contrast to other modern societies, such as Denmark. To address this discrepancy, we investigated the natural history of HBV infection in Greenland by estimating the age-specific incidence of HBV infection, the proportion of chronic carriers, and the rates of hepatitis B surface antigen seroclearance. In total, 8,879 Greenlanders (16% of the population) from population-based surveys conducted in 1987 and 1998 were followed through March 2010. Data on HBV status were supplemented by HBV test results from all available HBV registries in Greenland to determine changes in HBV status over time. Incidence rates of HBV infection and hepatitis B surface antigen seroclearance were estimated after taking into account interval censoring. The incidence of HBV infection in 5–14-year-old subjects was less than 1 per 100 person-years and peaked at 5 per 100 person-years in persons 15–24 years of age. Overall, 17.5% of persons infected in adulthood were estimated to become chronic carriers. HBV is primarily transmitted in adolescence and adulthood in Greenland. In contrast to what is observed in most other populations, HBV-infected adults in Greenland have a high risk of progressing to chronic HBV carriage. This phenomenon might explain how the high rate of infection is maintained in Greenland.